2007
DOI: 10.1158/0008-5472.can-06-3732
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide Inhibits Tubulin Carboxypeptidase Activity

Abstract: Microtubules are centrally involved in cell division, being the principal components of mitotic spindle. Tubulin, the constituent of microtubules, can be cyclically modified on its A-subunit by enzymatic removal of the COOH-terminal tyrosine residue by an ill-defined tubulin carboxypeptidase (TCP) and its readdition by tubulin tyrosine ligase (TTL). We and others have previously shown that suppression of TTL and resulting accumulation of detyrosinated tubulin are frequent in human cancers of poor prognosis. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 50 publications
9
75
0
1
Order By: Relevance
“…As parth was given immediately before I/R, and on the basis of the results of prior studies and the results of our experiments, we believe that the effect of parth was both lasting and substantial [43]. Although parth is recognized as an IkB kinase complex inhibitor [28], recent studies [44,45] suggest that parth could affect other pathways without inhibiting NF-kB. Finally, another control group, that of SPC þ vehicle given 48 h prior to I/R, was not included as the vehicle used in this study has not shown any protective effects in prior studies [28,46].…”
Section: Discussionsupporting
confidence: 49%
“…As parth was given immediately before I/R, and on the basis of the results of prior studies and the results of our experiments, we believe that the effect of parth was both lasting and substantial [43]. Although parth is recognized as an IkB kinase complex inhibitor [28], recent studies [44,45] suggest that parth could affect other pathways without inhibiting NF-kB. Finally, another control group, that of SPC þ vehicle given 48 h prior to I/R, was not included as the vehicle used in this study has not shown any protective effects in prior studies [28,46].…”
Section: Discussionsupporting
confidence: 49%
“…PTL decreases also the activity of histone deacetylase (HDAC) (Gopal et al 2007) and DNA methyltranspherase 1 (DNMT1) (Liu et al 2009). Furthermore, PTL can interfere with microtubule function through tubulin binding (Fonrose et al 2007). However, the main mechanism of PTL action is linked to the inhibition of NF-κB (Rüngeler et al 1999).…”
Section: Parthenolide-the Most Studied Sesquiterpene Lactonementioning
confidence: 99%
“…Studies have shown that parthenolide actively interferes with microtubule formation [47] by reducing impaired control of spindle positioning. As spindle positioning is a factor favoring tumor invasiveness in cancer cells [47,48], microtubles may be a good target for cancer therapy. Chemical agents that primarily target cell cycle machinery are assumed to be potent anti-cancer drugs [48,49].…”
Section: Parthenolide Interferes With Microtubule Formationmentioning
confidence: 99%